Structure-activity relationship, bioactivities, molecular mechanisms, and clinical application of nuciferine on inflammation-related diseases - Tong Zhao; Yuchen Zhu; Rui Zhao; Shiyi Xiong; Jing Sun; Juntao Zhang; Daidi Fan; Jianjun Deng; Haixia Yang (Elsevier, 2023)
Nuciferine aporphine alkaloid mainly exists in Nelumbo nucifera Gaertn and is a beneficial to human health, such as anti-obesity, lowering blood lipid, prevention of diabetes and cancer, closely associated with inflammation. Importantly, nuciferine may contribute to its bioactivities by exerting intense anti-inflammatory activities in multiple models. However, no review has summarized the anti-inflammatory effect of nuciferine. This review critically summarized the information regarding the structure-activity relationships of dietary nuciferine. Moreover, biological activities and clinical application on inflammation-related diseases, such as obesity, diabetes, liver, cardiovascular diseases, and cancer, as well as their potential mechanisms, involving oxidative stress, metabolic signaling, and gut microbiota has been reviewed. The current work provides a better understanding of the anti-inflammation properties of nuciferine against multiple diseases, thereby improving the utilization and application of nuciferine-containing plants across functional food and medicine.